TINJAUAN PUTUSAN PERKARA NOMOR : 3096 K/PID.SUS/2018 DIKAITKAN DENGAN KITAB UNDANG-UNDANG HUKUM ACARA PIDANA - Sofi Ayu Anggraini; Mexsasai Indra; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
This study aims to determine how the Review of Case Decisions Number:3096 K/Pid.Sus/2018 is related to the Criminal Procedure Code. The formulationof the problem posed is How is the case verdict Number: 3096 K/Pid.Su/2018related to the Criminal Procedure Code and how is the concept of the idealdecision in case decision Number: 3096 K /Pid.Sus /2018 related to justice.This type of research can be classified in the type of normative research.In this study, the focus is on studying legal synchronization, by comparing theCriminal Procedure Code with Judges' Decisions. The approach taken includesthe literature approach. The data source used is secondary data consisting ofprimary legal materials, secondary legal materials, tertiary legal materials. Thetechnique of collecting data from this research is the literature review method,after the data is collected then it is analyzed to draw conclusions. The theory usedin this research is law enforcement theory and justice theory.First Travel case verdict Number: 3096 K / Pid.Sus / 2018 is linked to theCriminal Procedure Code, based on the Criminal Procedure Code, the assets arereturned to the rightful person, namely the First Travel congregation if the objectis confiscated for the state only items intended to be destroyed or damaged.Therefore, the decision stating that the state has the right to seize the assets is notin accordance with the Criminal Procedure Code.Concept of Ideal Decisions in case decisions Number: 3096 K / Pid.Sus /2018 in accordance with Law Number 48 of 2009 concerning Judicial PowerJudges must give decisions that are in accordance with the law from a sense ofpublic justice and require judges to understand the feeling of law and sense ofjustice who live in society.Keywords: Decisions, Assets, Fraud, Money Laundering, and the CriminalProcedure Code